Предмет: Алгебра,
автор: Аноним
Довести тотожність 1) 2 (a + b + c) – (a + b - c) - (a – b + c) = 2 ( b + c )
2) 1 – x – ( 1 – ( 1 – ( 1 – x ))) = 0
Ответы
Автор ответа:
0
Объяснение:
1)2a+2b+2c-a-b+c-a+b-c=2(b+c)
2a-a-a=0
2b-b+b=2b
2c+c-c=2c
виносимо спільний множник за дужки
2(b+c)
доведено
2)1-x-(1-(1-(1-x)))=0
1-x-1+1-1+x=0
1-1+1-1=0
-x+x=0
доведено
Похожие вопросы
Предмет: Литература,
автор: plotnikovd946
Предмет: Информатика,
автор: Аноним
Предмет: География,
автор: dima666ftv
Предмет: Биология,
автор: Девочка00909
Предмет: Українська мова,
автор: Bilhcak